Literature Study Of The Incidence Of Toxoplasmosis In Pigs - Melly Chaterina Outang; Diana Agustiani Wuri; Julianty Almet (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii. Cats are the main or definitive host of T. gondii. This study was conducted with the aim of looking at the level of Toxoplasmosis incidence in pigs in several regions in Indonesia and to see the relationship between risk factors and the incidence of Toxoplasmosis in pigs. The prevalence of Toxoplasmosis in pigs in several regions in Indonesia varies. The highest prevalence is in the Baliem Valley with a prevalence of 75.9%, while the lowest prevalence of pigs infected with T. gondii was in Manado, which was 0%. Risk factors that affect the incidence of toxoplasmosis in pigs are the presence of cats as the definitive host, maintenance, temperature and humidity, meanwhile, age has no effect on the incidence of toxoplasmosis in pigs.